Analisis Arsitektur Perumahan di Depan Danau Kawasan BSB Harmoni Modernitas dan Alam - Ammar Halimi; Nur Ilham (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
Housing in the BSB (Bukit Semarang Baru) area, located right in front of the lake, offers an architectural idea that combines the comfort of modern housing with a natural touch. In this analysis, several important architectural elements such as the use of foot plate foundations, construction time, and the use of wood planks on the building facade are explored to understand how this design combines functional and aesthetic aspects. This study aims to analyze these elements, especially in relation to spatial planning, functionality, and aesthetics, as well as how the integration between building architecture with the elements of the lake and the surrounding green space. Through a qualitative approach and direct observation, this paper offers a critical view of the concept of sustainability applied in the design of this area.